Cathode–Electrolyte Interface Modification by Binder Engineering for High‐Performance Aqueous Zinc‐Ion Batteries. Issue 5 (16th December 2022) - Dong, Haobo; Liu, Ruirui; Hu, Xueying; Zhao, Fangjia; Kang, Liqun; Liu, Longxiang; Li, Jianwei; Tan, Yeshu; Zhou, Yongquan; Brett, Dan J.L.; He, Guanjie; Parkin, Ivan P.
Abstract: A stable cathode–electrolyte interface (CEI) is crucial for aqueous zinc‐ion batteries (AZIBs), but it is less investigated. Commercial binder poly(vinylidene fluoride) (PVDF) is widely used without scrutinizing its suitability and cathode‐electrolyte interface (CEI) in AZIBs. A water‐soluble binder is developed that facilitated the in situ formation of a CEI protecting layer tuning the interfacial morphology. By combining a polysaccharide sodium alginate (SA) with a hydrophobic polytetrafluoroethylene (PTFE), the surface morphology, and charge storage kinetics can be confined from diffusion‐dominated to capacitance‐controlled processes. The underpinning mechanism investigates experimentally in both kinetic and thermodynamic perspectives demonstrate that the COO − from SA acts as an anionic polyelectrolyte facilitating the adsorption of Zn 2+ ; meanwhile fluoride atoms on PTFE backbone provide hydrophobicity to break desolvation penalty. The hybrid binder is beneficial in providing a higher areal flux of Zn 2+ at the CEI, where the Zn‐Birnessite MnO2 battery with the hybrid binder exhibits an average specific capacity 45.6% higher than that with conventional PVDF binders; moreover, a reduced interface activation energy attained fosters a superior rate capability and a capacity retention of 99.1% in 1000 cycles. The hybrid binder also reduces the cost compared to the PVDF/NMP, which is a universal strategy to modify interface morphology. Abstract : Intensive efforts are applied to cathode, anode, and electrolyte, while it still lacks a comprehensive understanding of the interface mechanisms. Herein, a universal strategy is proposed for stabilizing the cathode directly from interface modification by the binder interface engineering. After introducing anionic polyelectrolyte in the binder, the battery interface mechanism can be tuned between diffusion control and capacitive dominance.